الحماية الجنائية للخلايا الجذعية: دراسة مقارنة - فهمي، دينا عبدالعزيز Fahmi, Dina Abdulaziz (جامعة المنصورة - مركز تطوير الأداء الجامعي, 2021)
Stem cells are the basic cells that make up the human body, scientists called stem cells described Lady cells as characterized by its propensity to transform into any type of body cells through specific environmental parameters in the laboratory, and headed scientists and doctors used to treat many diseases that do not have A treatment, or alternative to, human organ and tissue transplantation In spite of that, freedom in the normal situation, as opposed to freedom in return, in exchange for housing, our plans, plans, plans, plans, plans, plans, and current plans, which is in coordination. Between the law and medical developments without neglecting the principles of Islamic law in these actions, especially as the acceptance of public opinion and modern medical developments depends on their extent in light of the principles of our society
الخلايا الجذعية هي الخلايا الأساسية التي يتكون منها جسم الإنسان، وأطلق العلماء على الخلايا الجذعية تميز بقابليتها للتحول إلى أي نوع من خلايا الجسم من خلال معاملات بيئية محدده في واتجه العلماء والأطباء في استخدامها لعلاج العديد من الأمراض التي لا يوجد لها علاج، أو بديل عن زرع الأعضاء والأنسجة البشرية. إن الواقع العملي يكشف لنا سلبيات هذه الاكتشافات العلمية التي يتعين التصدي لها بالحماية الجنائية ووضع ضوابط دقيقة لممارستها، وهذا لأمر ليس بالسهل لتعدد زواياه الطبية والقانونية واتسام القواعد القانونية بالثبات النسبي، على خلاف الأساليب الطبية إنها في تطور مستمر، الأمر الذي يوجب التنسيق بين القانون والتطورات الطبية دون إغفال مبادئ الشريعة الإسلامية في تلك الأعمال، خاصة وأن تقبل الرأي العام لهذه التطورات الطبية الحديثة يعتمد على مدى مشروعيتها في ضوء مبادئ مجتمعنا.
Keywords: الخلايا الجذعية -- الشريعة الاسلامية -- القوانين الجنائية